EFFICIENCY ALLOCATIVE NION FARMING IN TYE DISTRICT BANTUL - Alfian Yunianto nugroho; Slamet Hartono; Masyhuri Masyhuri (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2013)
This aim of this study is to know the factors affecting onion production, the efficiency of the use of factors production on onion farming and to analyze the factors that affect onions farm incomes. The research was conducted in the district of Bantul with a sample of 30 farmers, factors affecting onion production was analyzed with multiplr linear regression analysis (method Cobb-Douglas) production function, allocative efficiency of the use of production factors by calculating an index value of allocative efficiency, the factors that influenced farm onion incomes anlayzedmultiple linear regression analysis (method Cobb-Douglas function of income). Production factors influence positive effect on onion productionin the district of Bantul are seedsm fertilizer NPK, KCl, soil and pesticides, input allocation of land, seed, fertilizer KCl.NPK fertilixer and fungicide antracol phonska have not be efficient so they need to be improved, the income of farmers affected by land area and the price of NPK phonska and insecticida.